Exploring the link between work-related psychosocial factors and professional quality of life among ethiopian healthcare workers: Insights from structural equation modelling analyses - Yitagesu Habtu; Abera Kumie; Medhine Selamu; Mirgissa Kaba; Hidenori Harada; Eshetu Girma (PLoS ONE, 2025)
Background Work-related psychosocial factors increase the likelihood of poor professional quality of life (PQoL) outcomes, which are composed of three subscales burnout (BO), compassion fatigue(CF), and low compassion satisfaction (CS). However, studies on the impact of work-related psychosocial factors and the mediating role of workplace social support on PQoL in Ethiopian healthcare workers are limited. Therefore, our study aimed to explore the link between work-related factors and three subscales of PQoL, and assess the mediational role of workplace social support. Methods We used a cross-sectional study design in selected public hospitals in Central and Southern Ethiopia between January and February 2023. We used a stratified random multistage sampling technique to select participants. We collected data on our endogenous variables using the PQoL-9 and data on exogenous work-related psychosocial variables using psychometrically validated scales. The data were entered using Epi-info 7 and exported to JAMOVI 2.4.14 for structural equation modelling. Results A total of 1426 healthcare workers participated in the study. Among health workers, 25.5% experienced burnout above the third quartile, 24.8% had compassion fatigue above the third quartile, and nearly half scored below the third quartile for compassion satisfaction. Healthcare workers’ exposure to higher job demands (β=0.186) and work-family conflict (β =  0.306) were positively associated with BO, while decision latitude (β = -0.133), social support (β = -0.178), and job rewards (β = -0.170) were negatively associated. Decision latitude (β = -0.186), job rewards (β = -0.227), and social support (β = -0.152) are negatively associated, and work-family conflict (β =  0.367), and job effort (β =  0.067) positively associated with CF. Regarding CS, social support (β =  0.305), decision latitude (β = 0.262), and job rewards (β = 0.068) were positively associated, while work-family conflict (β =  -0.199) was negatively associated. Conclusion Our study highlighted the importance of promoting workplace interventions among healthcare workers to reduce BO, and CF, and increase CS. Various job rewarding strategies including revising current salary evaluation and grading systems, incentive packages, and recognition systems are required to improve health workers’ PQoL. Interventions focusing on work-family balance, workload management skills, technical job decision latitude skills and task force allocation may be required to optimize job demands and controls.